A LINGUISTIC POLITENESS: AN ANALYSIS OF GENDER DIFFERENCES IN SPEAKING CLASSROOM - Syafrizal, SYAFRIZAL; Putri, Fianika Sya'bana (Universitas Nusantara PGRI Kediri, 2020)
Communicative competence underlines that grammatical knowledge is not enough to interact adequately, and thus includes pragmatic skills. For example, several communication errors, for confusion, may take place without logical understanding. Furthermore, politeness is an essential component of pragmatic competence. Many work has been carried out in this area, but few have shown the differences between the linguistic politeness of the language of male and female in the speaking classroom, while its primary findings are statements. Such work is carried out in the speaking classroom of university students, in particular in the sense of global foreign affairs. The statement is based on the Bacha, Bahous & Diab (2012) translation from DCT. In addition, certain politeness hypotheses are used to interpret the results. The studies have shown that women are more respectful than male students in general. Finally, teachers will comprehend this reality since they do not require male students to be as respectful as girls, they are practically peculiar.